Calcific Enthesitis of Lateral Patellofemoral Ligament: A Rare Cause of Anterolateral Knee Pain - Mettu, Sindhura; Shirodkar, Kapil; Henderson, Robert; Iyengar, Karthikeyan P.; Botchu, Rajesh (Indian Journal of Radiology and Imaging, 2024)
Hydroxyapatite deposition disease is a common musculoskeletal pathology that often affects rotator cuff tendons in the shoulder joint. Here, we present the first documented case of acute calcific enthesitis involving the lateral patellar retinaculum, specifically the lateral patellofemoral ligament (LPFL). A 35-year-old male presented with insidious onset atraumatic pain persisting for 3 months on the lateral aspect of the knee, intensifying over the past week. Clinical examination revealed focal tenderness in the anterolateral region of the knee, with no signs of patellar instability. Magnetic resonance imaging was performed, which revealed thickening and calcification within the LPFL and perilesional edema, further confirmed on computed tomography and ultrasonography. Patient was managed successfully with barbotage with complete resolution of symptoms. This case highlights the importance of considering calcification of LPFL in the differential diagnosis of anterolateral knee pain and underscores the importance of different imaging modalities for prompt diagnosis.
Keywords: periarthritis; HADD; knee; USG; patellar retinaculum; MRI; calcific enthesitis